Refugee crisis in Europe – a new challenge of the XXI century - Kopei, Yuliia (Lviv Polytechnic Publishing House, 2016)
The problem of refugees has been existed during centuries but nowadays it becomes more and more actual. It becomes one of the values that are of top priority for many developed countries. The paper depicts situation concerning the refugees crisis in Europe, gives statistics about amount of refugees in different European countries and also suggests ways of solution of this problem.
Keywords: refugees; migrants; crisis; Europe; Syria